In search of hidden rules : Genre-specific conventions in the Finnish translations of comics - Vainionpää, Tauno (My University, 2020)
In this study, I study the Finnish translations of graphic novels and comic strips in order to determine whether or not the translators of the two genres follow some conventional genre-specific rules. In order to find such conventional genre-specific rules, I will study proper nouns and the translation strategies that have been applied to them in the translations of two graphic novel series and two comic strip series. Analysis will first consider each individual series, then look at both genres on their own and finally compare the genres to each other as well as the material as a whole. The final results of the study did not show strong proof of any tendencies in translation that were characteristic to one single genre. Since this does not prove that such genre-specific tendencies do not exist, further studies with larger material and larger scope are recommended.
Keywords: translation, onomastics, comics, graphic novels, comic strips, strategies, proper nouns, domestication, foreignization